UNSUR ASMARA DAN DENDAM DALAM NOVEL LES LIAISONS DANGEREUSES KARYA CHODERLOS DE LACLOS - Bandu, Irianti; Agustina, Muttiara; Adi Armin, Mardi (JURNAL ILMU BUDAYA, 2025)
This study analyses the intrinsic elements of romance and revenge in Choderlos de Laclos’s epistolary novel, Les Liaisons Dangereuses. By employing theories of characterization, personality, and theme, the research investigates how main characters, specifically Marquise de Merteuil and Vicomte de Valmont, manipulate love to achieve retribution . The study utilizes a descriptive analysis method to deconstruct the psychological motives behind their actions. Results indicate that romance is not portrayed as genuine affection but as a strategic tool for power, where the epistolary format amplifies the realism of the characters' deceit and moral corruption . Consequently, the novel functions as a sharp social critique of the 18th-century French aristocracy, demonstrating how the interplay of calculated seduction and vengeance leads to inevitable destruction.